1985
DOI: 10.1207/s15327752jpa4906_16
|View full text |Cite
|
Sign up to set email alerts
|

Vivid Persuasion in the Courtroom

Abstract: When witnesses at a trial offer testimony that is vivid, it may be more persuasive than the same testimony offered in a pallid manner. In this paper we elucidate three categories of variables (inferential, attentional/memorial, and affective) that are likely to mediate the effects of the vividness of testimony on jury judgments. These variables are then used to explain discrepant findings among mock juror experiments investigating vividness effects. Finally, we discuss the implications of vividness effects for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
48
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(49 citation statements)
references
References 11 publications
1
48
0
Order By: Relevance
“…With respect to central route processing, visual displays tend to be more vivid than words alone (see Bell & Loftus, 1985); by attracting and holding jurors' attention, slide shows would be predicted to improve jurors' retention and possibly their understanding of the information displayed. Some research on courtroom technologies other than PowerPoint, for instance, computer animations, has found limited enhancement of recall of key information (Dahir, 2005;Morell, 1999).…”
mentioning
confidence: 99%
“…With respect to central route processing, visual displays tend to be more vivid than words alone (see Bell & Loftus, 1985); by attracting and holding jurors' attention, slide shows would be predicted to improve jurors' retention and possibly their understanding of the information displayed. Some research on courtroom technologies other than PowerPoint, for instance, computer animations, has found limited enhancement of recall of key information (Dahir, 2005;Morell, 1999).…”
mentioning
confidence: 99%
“…Support for this reasoning comes from the comparison of participants' pre-and post-line-up guilt judgements. Only the negative outcome information caused a signifi cant change in perceived guilt, suggesting that participants in this condition indeed paid more attention to the line-up outcome; research on information integration has shown that the amount of attention and elaboration spent on a piece of information predicts its impact on a fi nal judgement (Anderson, 1996;Bell & Loftus, 1985;Tesser & Conlee, 1975). In sum, the above interpretation of the fi ndings of Experiment 2 imply that the effect of positive outcome information should be stronger in investigations with less incriminating evidence, where investigators have less pronounced guilt presumptions towards the suspect.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, visual displays can (as was noted above) enhance jurors' attention and recall (Bell & Loftus, 1985), which would be predicted to improve their ultimate judgments. Visuals can also increase jurors' level of engagement, motivating them to decide more accurately (see Chaiken, 1980).…”
Section: Beneficial Effectsmentioning
confidence: 89%
“…Even where it is not necessarily the focal point of the case, visual evidence would likely influence decision makers' thoughts and feelings and, hence, their verdicts. Because still or moving pictures can be more vivid than oral testimony or text, for instance, visual evidence could well be more memorable and/or lead to stronger emotional responses (see Bell & Loftus, 1985), either of which could affect the outcome. Personal injury lawyers often present day-in-the-life movies of an accident or malpractice victim (e.g., Joseph, 1997), presumably because they believe that the movies give jurors a better understanding of the extent of the victim's injuries and/ or encourage them to sympathize with the victim, leading to larger damage awards.…”
Section: Varieties Of Visual Evidencementioning
confidence: 99%